Some selected properties of bamboo thermoplastic composite: Influence of particle size, filler loading and maleated anhydride polypropylene addition / Jamaludin Kasim …[et al.] - Kasim, Jamaludin; Dhalan, Khairul Zaman; Harun, Jalaluddin; Ashaari, Zaidon; Mohmod, Abd. Latif; Mohd Yusof, Mohd Nor (Universiti Teknologi MARA Cawangan Pahang, 2003)
Bamboo particles were used as filler in the manufacture of bamboo-polypropylene thermoplastics composite. Bamboo particles of three different particle size (0.12, 0.18 &0.25 mm), filler loading of 10,30 and 50% and maleated anhydride polypropylene at 3% was used in the study. An increase in particle size use decreased significantly all the mechanical properties of tensile, flexural and elongation at break, while the water absorption increased. Increasing the filler loading from 10 to 50% decrease the tensile strength (33.8%). Flexural (47.6%) and elongation at break by 70%, while the water absorption increased from 0.19 to 1.65%. The addition of 3% maleated anhydride polypropylene increased the tensile, flexural strength and decreased the water absorption significantly